Factors affecting patients' journey with primary healthcare services during mental health‐related sick leave - Justine Labourot; Émilie Pinette; Nadia Giguère; Matthew Menear; Cynthia Cameron; Elyse Marois; Brigitte Vachon (Wiley, 2024)
Abstract Context Best practice guidelines for the recovery and return to work (RTW) of people with mental disorders recommend access to the services of an interdisciplinary team combining pharmacological, psychological and work rehabilitation interventions. In the Canadian context, primary healthcare services are responsible for providing these services for people with common mental disorders, such as depressive or anxiety disorders. However, not everyone has easy access to these recommended primary healthcare services, and previous studies suggest that multiple personal, practice‐related and organizational factors can influence the patient's journey. Moreover, previous studies documented that family physicians often work in silos and lack the knowledge and time needed to effectively manage by themselves patients' occupational health. Thus, the care and service trajectories of these patients are often suboptimal and can have important consequences on the person's recovery and RTW. Objective and Population Studied Our study aimed to gain a better understanding of the patient journeys and the factors influencing their access to and experience with primary healthcare services while they were on sick leave due to a common mental disorder. Methods A descriptive qualitative research design was used to understand and describe these factors. Conventional content analysis was used to analyze the verbatim. Results Five themes describe the main factors that influenced the patient's journey of the 14 participants of this study: (1) the fragmented interventions provided by family physicians; (2) patients' autonomy in managing their own care; (3) the attitude and case management provided by the insurer, (4) the employer's openness and understanding and (5) the match between the person's needs and their access to psychosocial and rehabilitation services. Conclusions Our findings highlight important gaps in the collaborative practices surrounding the management of mental health‐related sick leave, the coordination of primary healthcare services and the access to work rehabilitation services. Occupational therapists and other professionals can support family physicians in managing sick leaves, strengthen interprofessional and intersectoral collaboration and ensure that patients receive needed services in a timelier manner no matter their insurance coverage or financial needs. Patients of Public Contribution This study aimed at looking into the perspective of people who have lived or are currently experiencing a sick leave related to a mental health disorder to highlight the factors which they feel hindered their recovery and RTW. Additionally, two patient partners were involved in this study and are now engaged in the dissemination of the research results and the pursuit of our team research programme to improve services delivered to this population.